Chronic Supplementation With a Mitochondrial Antioxidant (MitoQ) Improves Vascular Function in Healthy Older Adults. Issue 6 (June 2018) - Rossman, Matthew J.; Santos-Parker, Jessica R.; Steward, Chelsea A.C.; Bispham, Nina Z.; Cuevas, Lauren M.; Rosenberg, Hannah L.; Woodward, Kayla A.; Chonchol, Michel; Gioscia-Ryan, Rachel A.; Murphy, Michael P.; Seals, Douglas R.
Abstract : Excess reactive oxygen species production by mitochondria is a key mechanism of age-related vascular dysfunction. Our laboratory has shown that supplementation with the mitochondrial-targeted antioxidant MitoQ improves vascular endothelial function by reducing mitochondrial reactive oxygen species and ameliorates arterial stiffening in old mice, but the effects in humans are unknown. Here, we sought to translate our preclinical findings to humans and determine the safety and efficacy of MitoQ. Twenty healthy older adults (60–79 years) with impaired endothelial function (brachial artery flow–mediated dilation <6%) underwent 6 weeks of oral supplementation with MitoQ (20 mg/d) or placebo in a randomized, placebo-controlled, double-blind, crossover design study. MitoQ was well tolerated, and plasma MitoQ was higher after the treatment versus placebo period ( P <0.05). Brachial artery flow–mediated dilation was 42% higher after MitoQ versus placebo ( P <0.05); the improvement was associated with amelioration of mitochondrial reactive oxygen species–related suppression of endothelial function (assessed as the increase in flow-mediated dilation with acute, supratherapeutic MitoQ [160 mg] administration; n=9; P <0.05). Aortic stiffness (carotid–femoral pulse wave velocity) was lower after MitoQ versus placebo ( P <0.05) in participants with elevated baseline levels (carotid–femoral pulse wave velocity >7.60 m/s; n=11). Plasma oxidized LDL (low-density lipoprotein), a marker of oxidative stress, also was lower after MitoQ versus placebo ( P <0.05). Participant characteristics, endothelium-independent dilation (sublingual nitroglycerin), and circulating markers of inflammation were not different (all P >0.1). These findings in humans extend earlier preclinical observations and suggest that MitoQ and other therapeutic strategies targeting mitochondrial reactive oxygen species may hold promise for treating age-related vascular dysfunction. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02597023. Abstract : Supplemental Digital Content is available in the text.